2013
DOI: 10.1111/adj.12027
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Streptococci to various orthodontic composite resins

Abstract: Background: This investigation aimed to determine quantitatively the adhesion of Streptococcus mutans and Streptococcus sobrinus to orthodontic composite resins that were tested simultaneously using radio-markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…It has been reported that glass ionomer and resin composites have a tendency to collect more plaque or microor-ganisms than different restorative materials in vivo and in vitro (30). The adhesion of microorganisms to the orthodontic composite resin is attributed to van der Waals forces, as well as hydrophobic and electrostatic factors, and Streptococcus mutans adhesion to composite resin is greater than to orthodontic appliances (31). In the present study, excess adhesive was removed from around the brackets during the bonding process to simulate clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that glass ionomer and resin composites have a tendency to collect more plaque or microor-ganisms than different restorative materials in vivo and in vitro (30). The adhesion of microorganisms to the orthodontic composite resin is attributed to van der Waals forces, as well as hydrophobic and electrostatic factors, and Streptococcus mutans adhesion to composite resin is greater than to orthodontic appliances (31). In the present study, excess adhesive was removed from around the brackets during the bonding process to simulate clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The number of S. mutans and S. sobrinus microorganism in stimulated saliva samples does not appear to be significantly different between patients with stainless steel brackets and patients with plastic brackets [36] . Enlight orthodontic composite resin has less adhesion of S. sobrinus and S. mutans which may reduce enamel demineralization and risk of white spot formation [37] .…”
Section: Diagnosismentioning
confidence: 99%
“…Biofilm has a crucial role in the adhesion of these microorganisms to the dental surface [2,3]. Enamel demineralization is caused by the organic acids produced by various microorganisms, mainly Streptococcus mutans (S. mutans) and Streptococcus sobrinus (S. sobrinus), which are identified as the main pathogens in dental caries [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Orthodontic treatment, using fixed appliances (brackets, bands, archwires, ties), provides suitable conditions to bring about the colonization of cariogenic microorganisms. Because fixed appliances promote the retention and adhesion of biofilm, dental hygiene becomes more complicated, and microorganisms increase the risk of enamel demineralization [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation